The Role of Relative Wages and Excess Demand in the Sectoral Flow of Labour - Pissarides, C. A. (Review of Economic Studies, 1978)
Journal Article The Role of Relative Wages and Excess Demand in the Sectoral Flow of Labour Get access Christopher A. Pissarides Christopher A. Pissarides London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 453–467, https://doi.org/10.2307/2297248 Published: 01 October 1978 Article history Received: 01 February 1977 Accepted: 01 October 1977 Published: 01 October 1978